PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA PADA SUB POKOK BAHASAN KUBUS DAN BALOK DENGAN PENERAPAN MODEL PEMBELAJARAN CONCEPTUAL UNDERSTANDING PROCEDURES DI KELAS IX-B SMP NEGERI 2 TANTOM ANGKOLA - RISMA MASNAIRAN SIHOMBING (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
The problem in this study is the low learning outcomes of students in the sub-topic of cubes and blocks in class IXb of SMP Negeri 2 Tantom Angkola, to overcome this problem in this study the application of the Learning Model Conceptual Understanding Procedures. This research is a classroom action research, The results showed that by applying the Conceptual Understanding Procedures Learning Model, the results of the initial test showed that the lowest score was 45 and the highest score was 80. study completeness requirements) as many as 14 people (58.33%). And the mean value of the initial test score was 59.79. After giving the action in the first cycle, it was obtained an increase in student learning outcomes with a class average of 68.12. In the first learning outcomes test, it can be seen that 21 students (87.50%) have completed their studies and 3 students (12.50%) have not completed their studies. Based on the results of the research, it can be concluded that there is an increase in student learning outcomes on the sub-topic of cubes and blocks with the application of the Conceptual Understanding Procedures Learning Model in Class IXb of SMP Negeri 2 Tantom Angkola.